Descriptive characters of growth form in Poaceae-An overview - Perreta, Mariel Gladis (2011)
The architecture of the shoot branching system in Poaceae defines the growth forms within this family. The specific characteristics of the main axis as well as the disposition and characteristics of the lateral shoots determine the main structural variations found among species. In this work, we discuss the set of parameters to be taken into account in describing the vegetative structure of Poaceae in order to achieve a full diagnosis of the system and to thoroughly assess and interpret its variations.